RESISTANCE OF POTATO VARIETIES OF CONVENTIONAL BREEDING TO COLORADO POTATO BEETLE LEPTINOTARSA DECEMLINEATA SAY, 1824 (COLEOPTERA, CHRYSOMELIDAE) IN CONDITION OF PRIMORSK TERRITORY - N. V. Macishina (Овощи России, 2015)
Results of field experiments of the study of seasonal abundance of Colorado potato beetle in different potato varieties. It was shown that some varieties developed through conventional breeding are able keeping its resistance when threshold of harmfulness is exceed.